2022
DOI: 10.1038/s41467-022-29814-3
|View full text |Cite
|
Sign up to set email alerts
|

Toward azo-linked covalent organic frameworks by developing linkage chemistry via linker exchange

Abstract: Exploring new linkage chemistry for covalent organic frameworks (COFs) provides a strong driving force to promote the development of this emerging class of crystalline porous organic materials. Herein we report a strategy to synthesize COFs with azo linkage, one of the most important functional unit in materials science but having not yet been exploited as a linkage of COFs. This strategy is developed on the basis of in situ linker exchange, by which imine-linked COFs are completely transformed into azo-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 51 publications
(41 reference statements)
0
43
0
Order By: Relevance
“…Fourier transform extended X-ray adsorption fine structure (FT-EXAFS) spectroscopy was performed to obtain more detailed information on the coordination structure of Co on the sulfo-COF support [43].…”
Section: Coordination Environment Of Atomically Dispersed Comentioning
confidence: 99%
“…Fourier transform extended X-ray adsorption fine structure (FT-EXAFS) spectroscopy was performed to obtain more detailed information on the coordination structure of Co on the sulfo-COF support [43].…”
Section: Coordination Environment Of Atomically Dispersed Comentioning
confidence: 99%
“…The three-component Strecker reaction, aza-Diels-Alder reaction, Debus-Radziszewski reaction, sulfur cyclization reaction, Groebke-Blackburn-Bienayme ´reaction, A 3 -coupling reaction, and Kabachnik-Fields reaction have been used for COF synthesis with a-aminonitrile, 40 quinoline, 40 benzimidazole, 41 benzothiazole, 42 imidazo[1,2a]pyridine, 43 propargylamine 44 and a-aminophosphonate 45 linkages, respectively. In addition, the construction of COFs linked by amine, 46,47 amide 48,49 benzothiazole, 50 and azo 51 moieties based on post-synthetic modification of imine-linked COFs greatly enriched the variety of COFs.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the exchange of building blocks (linker exchange) in already existing, crystalline frameworks opens the possibility to synthesize COFs with improved crystallinity or make COFs accessible that were not accessible via condensation of the respective building blocks. , Qian et al reported the first COF-to-COF linker exchange by replacing 1,4-phenylenediamine (PA) with benzidine (BD) in an imine-linked COF, which yielded an almost complete transformation . The linker-exchange strategy was applied to achieve, among others, different COF linkages, , changes in the pore hierarchy and size by different linker symmetries, the transformation of linear polymers into COFs , or 3D into 2D COFs, and the introduction of functional groups into the framework …”
Section: Introductionmentioning
confidence: 99%